2012
DOI: 10.3390/app2040773
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Complex of β-Cyclodextrin and Disulfide Form of 4-Aminothiophenol

Abstract: An inclusion complex of β-cyclodextrin and 4-aminothiophenol was assembled by hydrophobic interaction of the host (β-cyclodextrin) and guest (4-aminothiophenol). The complex was isolated as crystalline solid and studied by single crystal X-ray diffraction method along with NMR and IR spectroscopy. Two cyclodextrin rings each containing one disulfide form of 4-aminothiophenol were found to pair up by hydrogen bonding of the outer rim -OH groups. The phenyl disulfide moiety of 4-aminophenyl disulfide molecule wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…27 Our recent study has also provided similar results. 42 Because the height of the cavity formed by a head-to-head dimer of βcyclodextrin (1.57 nm 43 ) is comparable to the acyl chain length of POPC, it is concluded that the acyl chains of POPC in the 1:4 complex are splayed apart, with each included within two MβCD molecules. 27 On the other hand, Tanhuanpaä̈et al have revealed that phospholipids, both of whose acyl chains are labeled with a pyrene moiety, can form a complex with two to three molecules of γ-cyclodextrin (which consists of eight glucose residues, whereas β-cyclodextrin consists of seven glucose residues) and that the complex formation enhances the excimer fluorescence, which indicates that the two pyrenelabeled acyl chains share the same γ-cyclodextrin cavity.…”
Section: Calculation Ofmentioning
confidence: 99%
“…27 Our recent study has also provided similar results. 42 Because the height of the cavity formed by a head-to-head dimer of βcyclodextrin (1.57 nm 43 ) is comparable to the acyl chain length of POPC, it is concluded that the acyl chains of POPC in the 1:4 complex are splayed apart, with each included within two MβCD molecules. 27 On the other hand, Tanhuanpaä̈et al have revealed that phospholipids, both of whose acyl chains are labeled with a pyrene moiety, can form a complex with two to three molecules of γ-cyclodextrin (which consists of eight glucose residues, whereas β-cyclodextrin consists of seven glucose residues) and that the complex formation enhances the excimer fluorescence, which indicates that the two pyrenelabeled acyl chains share the same γ-cyclodextrin cavity.…”
Section: Calculation Ofmentioning
confidence: 99%
“…As known in the literature, cyclodextrins (CD), the basket-like cyclic oligosaccharides consisting of 6 or more α-D-glucopyranoside units, have the cavity for inclusion and are of great interest in the food industry, medicine, pharmaceutical, agriculture etc. These types of cavities make CD as most suitable hosts for a number of molecules in a variety of applications [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…SSOS has been combined with other substances to successfully embed blackcurrant oil and lemon oil in a microcapsule core 14,15 . As a dextrin molecule having a hydrophilic appearance and a hydrophobic internal structure, β-cyclodextrin can form an inclusion complex with a guest molecule, re-sulting in a change in the physicochemical properties of the guest, which is widely used in the pharmaceutical field to improve the bioavailability of guest molecules 16,17 . The precursor of the microcapsule powder is a microcapsule emulsion.…”
mentioning
confidence: 99%